Strategi Guru Pendidikan Agama Islam Dalam Membentuk Sikap Tasamuh Peserta Didik di SD Negeri 1 Manyargading - Munawwaroh, Munisatul; Al Mufti, Alex Yusron (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2024)
Forming a tasamuh attitude of students in an educational institution is crucial, especially realized by PAI teachers in every educational institution. The aim of this research is to analyze the strategies of PAI educators in forming the tasamuh attitude of students, describe the form of tasamuh attitude of students, and identify the supporting and hindering factors of PAI educator in forming the tasamuh attitude of learner at SD Negeri 1 Manyargading. The method used is descriptive qualitative research. Data were accumulated by observation, interviews, and documentation. Data reduction, data display, and conclusions are the technical stages of data analysis used by researchers. The outcome of this research are that PAI teachers at SD Negeri 1 Manyargading have effective strategies in shaping students' tasamuh attitude, namely habituation strategies, sustainable internalization strategies, creative and fun learning strategies based on tasamuh values, media utilization strategies and learning facilities. The form of tasamuh attitude of learner at SD Negeri 1 Manyargading is that there are “social” activities, always visiting friends who are sick, not imposing opinions on other students, high respect between students and to the teachers and school staff. Supporting or enabling factors PAI teachers in forming the attitude of tasamuh of learner at SD Negeri 1 Manyargading are support of the school, especially the principal who always inspires and encourages the spirit of tasamuh to teachers and students while the inhibiting factor is the transformation in the attitude of students because their age is still in time of growth and development.